(untitled) (Heritage, 2023)
The latest Tesat report and statistical data analysis show that the individual exteremist actions are predominant in EU, mostly incentivized by social networks, especially Telegram groups after 2016. Consequently, French and German prime ministers took the inciative on 23rd August 2016 and induced legal regulations for Telegram group, especially concerning jihadist secret messages. Balkan as multiconfessional transitory area distinguishes itself by two-directional regrutations: towards Islamis State and toward EU, consenquently representing constant safety threat to EU countries. The latest regrutation statistical data analysis shows that the highest regrutation rate is in Kosovo and Metohija – 316 identified cases, Bosna and Hercegovina (240) and Albania (140). The highset returnee rate is also noticed in Kosovo and Metohija (37%), right behind Macedonia (60%). It is reasonable to assume regrutation and returnee numbers are higher in 2023, pointing out the necessity for the European legislative models concering terroristic contents regulation introduction in Serbian legislative system. The Byzantine sources of the eight to the tenth century analysis gives better understaning of the contemporary situation theological background along with fundamental differences between Islam and Christianity outline. References from the patristic writings of Saint John Damascus, Nicetas of Byzanium and Theodore Abu Qurrah. Two main distinctive contemporary qualities between Islam and Christianity, namely, Islamic Monotheism vs. Christian Triadologic concept and Islamic jihad are recognized during early stages of the Byzantine–Islamic dialog. The necessity for theological education enabling concrete discerning between extremist and moderate Islamic belief is also emphasized along with the EU knowledge of Islamic desecularization process stenghtening in Balkan.